2017
DOI: 10.1083/jcb.201604123
|View full text |Cite
|
Sign up to set email alerts
|

Novel function of a dynein light chain in actin assembly during clathrin-mediated endocytosis

Abstract: Actin-capping protein is a key component of the actin cytoskeleton at sites of clathrin-mediated endocytosis. Farrell et al. show that a newly discovered component of the endocytic machinery belongs to the dynein light chain family and regulates the recruitment of actin-capping protein in a dynein motor–independent manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(39 citation statements)
references
References 57 publications
6
33
0
Order By: Relevance
“…S. cerevisiae Bbc1 was also shown to recruit the Tda2-Aim21 complex, which regulates capping protein recruitment (Farrell et al, 2017;Shin et al, 2018). However, this role of Bbc1 has not yet been explored in S. pombe.…”
Section: Comparison With Budding Yeastmentioning
confidence: 99%
“…S. cerevisiae Bbc1 was also shown to recruit the Tda2-Aim21 complex, which regulates capping protein recruitment (Farrell et al, 2017;Shin et al, 2018). However, this role of Bbc1 has not yet been explored in S. pombe.…”
Section: Comparison With Budding Yeastmentioning
confidence: 99%
“…While this article was being assembled, Farrell et al (2017) reported the existence and characterization of the Aim21/Tda2 complex, its localization, and the structure of Tda2. We concur with much of their study and provide important new information about the mechanism of Aim21/Tda2 localization and uncover its function as a factor that regulates the assembly at the barbed end to balance the actin distribution between cables and patches.…”
Section: Introductionmentioning
confidence: 99%
“…This finding agrees with previous data in human cells that interaction of CP with CPI-containing proteins contributes to CP localization. The specific CP binding partners in actin patches are unknown in S. pombe, but may involve the homologue of S. cerevisiae Aim21, which was recently proposed to bind CP through the CPI-binding residues and contribute to its localization to actin patches [19], though this finding was not reproduced in a second study [20]. Consistent with this hypothesis, deletion of S. pombe Aim21 was identified in our genome-wide screen to have fusion defects [44].…”
Section: Cp-formin Competition Is Best Revealed In Cells In Which It mentioning
confidence: 68%
“…Indeed, CP carrying surface mutations that block CPI motif binding retain capping activity in vitro, but lose localization and function in vivo, indicating that binding partners are required for its activity in vivo [18]. Furthermore, the Aim21/Tda2 complex, which binds CP through the same surface residues, modulates CP recruitment and activity at actin patches in yeast [19,20]. By keeping filaments short, CP promotes Arp2/3 branching and plays a major role in the force production of dendritic networks [21].…”
Section: Introductionmentioning
confidence: 99%